Pengaruh Pengumuman Dividen, Ukuran Perusahaan Terhadap Harga Saham dengan Kebijakan Dividen Sebagai Moderasi - Febriani, Meri; Indrati, Menik (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
This study aims to analyze the effect of cum and ex-dividend dates and company size on stock prices using the Dividend Payout Ratio (DPR) as a moderating variable. This study uses multiple linear regression analysis with moderating variables on companies listed on the Indonesia Stock Exchange. This research is based on signaling theory, which states that dividend information can serve as a signal for investors in making investment decisions. The results of the study indicate that all independent and moderating variables in the model simultaneously have a significant influence on stock prices. This suggests that the regression model used in this study is valid and can comprehensively explain stock price variations. This study implies that companies need to develop a more structured financial communication strategy, particularly in the disclosure of dividend information. Not only should the timing of dividend distribution be communicated, but the number of dividends to be distributed should also be clearly communicated to strengthen investor response. The implementation of this strategy must be accompanied by compliance with OJK and IDX regulations to maintain market confidence and increase the value of company shares.